The Break Subtype of Affect-H in English And Buginese: Revisiting Dixon’s Theoretical Framework - Fadhillah, Nurul; Yassi, Abdul Hakim; Sahib, Harlinah (Hasanuddin University, 2021)
The objective of this research is to analyze the differences and the similarity of The Break Subtype of Affect-H in grammatical and semantical construction. This research use descriptive qualitative method. Primary data are the data in English and Buginese. To collect the data in English the researcher use C Corpus of Contemporary American English (COCA) and to collect data in Buginese language, the researcher recorded some native speakers of Buginese while using the break verbs in Buginese language. The secondary data are the data that were taken from journals, e-books, and articles. The collected data were analyzed by using Dixon’s theory of Break Subtype of Affect-H. The result of this research shows that there are 14 words in Buginese that are identical with the “Break” verb. They are mappakkasolang, ma’jemmu’, mapperra’, maruttung, massope/makkape’, mappue’, mappacippe, mappareppa’, malleppoang, mappa’bettu, mappaleppo’, mappaddempung, and ma’bettu. Construction I of break verb have the same meaning as construction II of mappakkasolang verb. They both means that someone break something by using another instrument. Construction II of break verb and mappakkasolang verb have different meanings. The sentence in Buginese means that someone break something on the table, but no conclusion can be taken about how someone broke the thing. As for the sentence in English it is obvious that someone accidentally put his/her nail inside a piece of wood and break it. Construction III of break verb is applicable but in the other hand, construction III of mappakkasolang verb is not a common way of saying that something is broken because another thing accidentally break it, as in Buginese sentence the role of breaking something is usually done by human, animals, disaster, or weather.